# Match the post#

#### ksdhart2

##### Senior Member
$$\displaystyle 0 + (1 + 2 + 34 + 5) \cdot 6 + 789 = 1041$$

$$\displaystyle 98 \cdot 7 + 6 \cdot 5 + 4 + 321 + 0 = 1041$$

#### Harry_the_cat

##### Senior Member
0! + (1 + 2 + 34 + 5)* 6+ 789 = 1042
987 + 6*5 + 4 * 3 * 2 + 1 - 0 = 1042

Last edited:

#### Harry_the_cat

##### Senior Member
-0! +12 + 345 + 678 +9 =1043
987 + 6 * 5 + 4 * 3 * 2 + 1 + 0! =1043

#### Harry_the_cat

##### Senior Member
0 + 12 +345 +678 + 9 = 1044
9 + 8 + 7 - 6 - 5 + 4 + 3 + 2^10 = 1044

#### Denis

##### Senior Member
Then f(0*1 +23-4*5+6789=1040
But Jomette, that is not fully bracketed: so zip yer trap!!

0*1 + 2 - 3 + 4^5 - 67 + 89 = 1045

-9 + 8 - 7 + 6 + 5*4 + 3 + 2^10 = 1045

Last edited:

#### Subhotosh Khan

##### Super Moderator
Staff member
“This is a song that never ends, Yes, it goes on and on my friends, some people started singing it—not knowing what it was, ... "

Moderator Edit: Harry the Cat lends Subhotosh a hand:

-0! + 1234 - 5! + 67 * (8-9) =1046

987 + 6 + 54 + 3 - 2 - 1 - 0! =1046

#### Denis

##### Senior Member
Subhotosh, you bad boy, you should have posted a solution
for 1046...you too can be replaced!!

0 + 1234 - 5! + 67*(8 - 9) = 1047

987 + 6 + 54 + 321*0 = 1047

#### Denis

##### Senior Member
0 + 1 - 2 + 3 + 4^5 - 67 + 89 = 1048

-[√9 - 8 + 7 + 6! * √(5 + 4)] + 3210 = 1048

#### Harry_the_cat

##### Senior Member
Filling in 1046 since it was too hard for Subho:
-0! + 1234 - 5! + 67 * (8-9) =1046
987 + 6 + 54 + 3 - 2 - 1 - 0! =1046
and
0! + 1 - 2 + 3 + 4^5 - 67 + 89 = 1049
987 + 6 + 54 + 3 - 2 + 1 + 0 = 1049

• Denis

#### Harry_the_cat

##### Senior Member
0 + 1 + 23 + 4^5 - 6 + 7 - 8 + 9 = 1050
(-9 - 8 - 7 + 6 + 543) * 2 * 1 + 0 = 1050

#### Denis

##### Senior Member
0! + 1 + 23 + 4^5 - 6 + 7 - 8 + 9 = 1051
(-9 - 8 - 7 + 6 + 543) * 2 * 1 + 0! = 1051

Phewwww.......worked hard on that one!!

#### ksdhart2

##### Senior Member
$$\displaystyle 0 + 123 + 4 \cdot 5 \cdot 6 \cdot 7 + 89 = 1052$$

$$\displaystyle 987 + 6 + 54 + 3 + 2 \cdot 1 + 0 = 1052$$

#### Denis

##### Senior Member
$$\displaystyle 0! + 123 + 4 \cdot 5 \cdot 6 \cdot 7 + 89 = 1053$$

$$\displaystyle 987 + 6 + 54 + 3 + 2 \cdot 1 + 0! = 1053$$

Phewwww......worked hard on that one too!!

#### ksdhart2

##### Senior Member
$$\displaystyle 0 + 1 + 234 + 5 \cdot 6 + 789 = 1054$$

$$\displaystyle 9 \cdot 8 + 7 + 654 + 321 + 0 = 1054$$

Last edited:

#### Denis

##### Senior Member
0! + .1 + 2^3 + 4^5 + 6 + 7 + 8 + .9 = 1055

.9 + 876 + 5! + 4! + 32 + .1 + 0! = 1055

#### ksdhart2

##### Senior Member
$$\displaystyle 0 + 12 + 34 \cdot 5 \cdot 6 + 7 + 8 + 9 = 1056$$

$$\displaystyle 987 + 6 + 5 × 4 × 3 + 2 + 1 + 0 = 1056$$

#### Denis

##### Senior Member
$$\displaystyle 0! + 12 + 34 \cdot 5 \cdot 6 + 7 + 8 + 9 = 1057$$

$$\displaystyle 987 + 6 + 5 × 4 × 3 + 2 + 1 + 0! = 1057$$

I'm lazzzzzyyyyyy........

#### ksdhart2

##### Senior Member
$$\displaystyle 0! + 12 \cdot 3 + 45 + 6 + 7 + 8 + 9 = 1058$$

$$\displaystyle 987 + 6 + 54 + 32 + 1 + 0! = 1058$$

#### Denis

##### Senior Member
-0! + (1 + 2)! - 34*5 + 6! + 7*8*9 = 1059

9 * 8 * 7 + 6 + 543 + (2 + 1)! + 0 = 1059

#### Harry_the_cat

##### Senior Member
0 + (1 + 2)! - 34*5 + 6! + 7*8*9 = 1060

9 * 8 * 7 + 6 + 543 + (2 + 1)! + 0! = 1060

(with thanks to Denis' 1059)